Balinese Emotion Lexicons: A Natural Semantic Metalanguage Approach - Sudipa, I Nengah (International Journal Linguistics of Sumatra and Malay, 2022)
Academics are always interested in debating the study of emotions across cultures and languages. This is due to the diverse ways that emotions can be expressed in different contexts and situations in each language and culture. This article aims to discuss the meaning of Balinese Lexicons dealing with emotions. The theory applied is Natural Semantic Metalanguage (NSM) with two at once approaches, namely mapping and explication. The results showed that there is something good happened, represented by the lexicons: demen, kendel, and lédang, and something bad happened: sebet, inguh, and gedeg. The most interesting findings are the lexicon angob ‘surprise’ having semantic feature of something good might happen and ngon ‘surprise’ due to the something bad might happen. This can be inferred that there is an in-between position, not something good nor bad happened in the concerned Balinese emotion lexicons.